Differentiation and Contractile Analysis of GFP‐Sarcomere Reporter hiPSC‐Cardiomyocytes. (24th January 2018) - Sharma, Arun; Toepfer, Christopher N.; Schmid, Manuel; Garfinkel, Amanda C.; Seidman, Christine E.
Abstract: Human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) represent a powerful cellular platform for illuminating mechanisms of human cardiovascular disease and for pharmacological screening. Recent advances in CRISPR/Cas9‐mediated genome editing technology underlie this profound utility. We have generated hiPSC‐CMs harboring fluorescently‐tagged sarcomeric proteins, which provide a tool to non‐invasively study human sarcomere function and dysfunction. In this unit, we illustrate methods for conducting high‐efficiency, small molecule‐mediated differentiation of hiPSCs into cardiomyocytes, and for performing non‐invasive contractile analysis through direct sarcomere tracking of GFP‐sarcomere reporter hiPSC‐CMs. We believe that this type of analysis can overcome sensitivity problems found in other forms of contractile assays involving hiPSC‐CMs by directly measuring contractility at the fundamental contractile unit of the hiPSC‐CM, the sarcomere. © 2018 by John Wiley & Sons, Inc.